Analysis of user influence in slashdot - Tan, Qian Ting. (2011)
The study accessed and analyzed the interaction between users of Slashdot, a popular science and technology-related news website based on its user comment activity. A social network graph is built by extracting and processing the comment and user information, with the users being connected by ties. The ties represent the interdependency between users, which can be both an implicit and explicit type of relationship. In this study, we explored one of the implicit relationships – user’s influence on fellow Slashdot users, based on a comparison of three factors: in-degree, out-degree and comment score. In-degree represents the popularity of a user’s comment; out-degree represents a user’s level of activeness; comment score represents quality of the comment. The result of the study is used to investigate the sustainability of user’s influence across topics. Several interesting observations were made in the data analysis process. First, a user of high popularity does not make him a good writer. Second, a user who is highly active does not mean that he is a good writer. Third, a user whose comment score is high does not always receive good responses.